2013
DOI: 10.2474/trol.8.76
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Structure Formed by Thickeners of Greases Using Atomic Force Microscope

Abstract: This paper describes an experimental study on quantitative evaluation of correlation between the structure formed by thickeners and yield stress of greases. In order to evaluate the thickener structures, untreated surface of greases was observed by using an atomic force microscope, and an index was obtained from AFM images to describe the degree of dispersion of the thickeners. The index physically represented both factors of shape and distribution of thickeners. The results for twelve types of lithium soap gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…However, the lubrication mechanism of greases is still not fully understood [1]. The behaviors of thickener [2,3], and resulting complex rheological properties of grease makes it almost impossible to make accurate prediction of the film thickness or the friction coefficient based on the existing hydrodynamic and EHL theories.…”
Section: Introductionmentioning
confidence: 99%
“…However, the lubrication mechanism of greases is still not fully understood [1]. The behaviors of thickener [2,3], and resulting complex rheological properties of grease makes it almost impossible to make accurate prediction of the film thickness or the friction coefficient based on the existing hydrodynamic and EHL theories.…”
Section: Introductionmentioning
confidence: 99%
“…Grease is composed of liquid-phase base oil and solid-phase thickener, each of which may include additives. It was revealed that thickener fibers form three-dimensional network structures by transmission electron microscopy (TEM) and scanning electron microscopy (SEM) [3] and, more recently, atomic force microscopy (AFM) and confocal laser fluorescence microscopy (CLFM) have visualized the three-dimensional network structures as they are in grease [4,5].…”
Section: Findings On Bleedingmentioning
confidence: 99%
“…It is a two phase system composed of fluid base oil that gives its lubricant behaviour (65-97%), fibres thickener that provides its consistency (3-30%) and additives (0-5%) that protect the rolling bearings from wear or limit the grease components degradation (Lugt, 2013). From structural analyses made by Scanning Electron Microscopy (SEM) or Atomic Force Microscopy (AFM), grease thickener appears as a solid-like material of fibres with random orientation containing the oil in the free space (Hokao et al, 2013;Mansot et al, 1989;Shuff and Clarke, 1991). In the literature, grease is considered as a colloid system for the following reasons: i) the fibres have colloidal sizes in two (more often than one) measuring directions; ii) the oil, as dispersion medium, is held in the cells of the three-dimensional grease skeleton (thickener fibres) by some adsorption bonds, and the remaining part, mechanically (Ishchuk, 2006).…”
Section: Introductionmentioning
confidence: 99%